(untitled) (Research, Society and Development, 2020)
Objective: to identify HIV-1 subtypes, evaluate the presence of antiretroviral resistance (DRM) mutations and estimate the resistance level of the mutant strains detected in pregnant women attended at the reference maternity in Piauí, northeastern Brazil. Methodology: Of the 873 pregnant women, 17 infected with HIV-1 were selected to participate in this study. Genotyping of HIV-1 was performed using nucleotide sequencing followed by phylogenetic analyzes to determine the viral subtype, including identification using the COMET online tool. DRM were defined using the Calibrated Population Resistance Tool program. Additional analyzes were also performed to check drug resistance in the pre-treatment using the Stanford HIVdb Program. Results: Subtype B was detected in all pregnant women infected with HIV-1. The prevalence of DRM was 11.8%. The L90M and K103N mutations were identified, with high (nelfinavir and nevirapine) and intermediate (indinavir and saquinavir) resistance to different antiretrovirals. Conclusion: This study identified important genetic information on HIV-1 in pregnant women in Piauí, which can assist in directing control and prevention measures for this viral infection.